Wind Drift Design Considerations for Steel Framed Structures - Kumar, Gaurav; Jha, Kumod Ranjan; Gaur, Kanishk; Kumar, Dinesh; Bhardwaj, Ojesvi (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2014)
The world is developing at a very fast pace, also population in urban areas is also increasing with it due to change in demographics, and thus strong and durable buildings are the need of the hour. The design of steel framed buildings must take into consideration the lateral drift of the structure due to wind loading and any serviceability issues that may arise from this lateral movement. This paper focuses on one of these issues, damage to nonstructural components. It is an important issue which may significantly impact the buildings structural performance and economy. Furthermore, because these serviceability issues are not codified, there is a wide variation among design firms in how they are dealt with, leading to a greater economic disparity.